Fatores psicossociais de proteção na relação professor e estudante a partir da pandemia de Covid-19 - Canedo, Uelinton de Oliveira (My University, 2025)
The student-teacher relationship is a subject of study in psychology and education. With the advent of the Covid-19 pandemic, significant changes have occurred in this relationship. This research analyzes the psychosocial protective factors that have strengthened the student-teacher relationship since the pandemic, from the teachers perspective in the final years of Elementary Education. The study has a quantitative approach, exploratory, and cross-sectional approach. Twenty-four teachers participated in the research, from private school in the city of Caxias do Sul - RS, who responded to two questionnaires each. Data was collected using the Student-Teacher Relationship Scale (ERPA). Data analysis was 9 performed using software SPSS® (Statistical Package for the Social Science, IBM® SPSS® Statistics v.21), developed by IBM®. Psychosocial protective factors at work and positive psychology are the main theoretical pillars supporting this research. The results identified affection, comfort and trust, physical and emotional contact, praise, positive reinforcement, synergy, and support as psychosocial protective factors that strengthen the student-teacher relationship in the final years of Elementary Education, particularly since the Covid-19 pandemic. It was undestood that a good student-teacher relationship has a low level of conflict and a high level os positive feelings, and this brings reflections to education and psychology professionals, as well as raise awareness of elements that can facilitate the teaching profession. [resumo fornecido pelo autor]
O relacionamento professor e estudante é objeto de estudo nas áreas da psicologia e da educação. Com o advento da pandemia Covid-19, houve significativas mudanças nessa relação. Esta pesquisa objetiva analisar fatores psicossociais de proteção que fortalecem a relação professor e estudante, a partir da pandemia Covid19, na percepção de professores do anos finais do Ensino Fundamental. A pesquisa tem abordagem quantitativa, de caráter exploratório e transversal. Partciparam da pesquisa vinte e quatro professores, de quatro escolas da rede particular de ensino da cidade de Caxias do Sul - RS, que responderam a dois questionários cada. Os dados foram coletados a partir da aplicação da Escala de Relacionamento Professor-Aluno (ERPA). A análise dos dados se deu através do software SPSS® (Statistical Package for the Social Science, IBM® SPSS® Statistics v.21), desenvolvido pela IBM®. Fatores psicossociais de proteção no trabalho e a Psicologia Positiva são os principais pilares teóricos que sustentaram a pesquisa. Como resultado identificou-se o afeto, conforto e confiança, contato físico e afetivo, elogio, reforço positivo, sinergia e acolhimento como fatores psicossociais protetivos que contribuem para fortalecer a relação professor e estudante dos anos finais do Ensino Fundamental, a partir da pandemia de Covid-19. Entendeu-se que uma boa relação professor e estudante tem baixo índice de conflito e alto indice de sentimentos positivos, e isso traz reflexões para profissionais da educação e da psicologia, além da consciência de elementos que facilitem o fazer laboral do docente. [resumo fornecido pelo autor]
Keywords: Psicologia educacional; Professores e alunos; Educação; Covid-19; Educational psychology; Teacher-student relationships; Education; Covid-19